ANALYSIS OF THE INFLUENCE OF MOTIVATION AND SOCIAL SUPPORT ON THE COMPETENCE OF NON-CIVIL SERVANT ISLAMIC RELIGIOUS INSTRUCTORS IN LANGKAT REGENCY - Ratna Herlina; Abdul Rahim Matondang; Nazaruddin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Religious Counselor is a position that is directly under the Ministry of Religion and is tasked with guiding, mobilizing and inviting the community both in social and religious affairs. The status of PAI employees besides PNS also includes PAI Non PNS who are Islamic Religious Counselors with honorary status. Currently, the performance of PAI Non PNS employees in Langkat Regency throughout 2020 to 2022 has been found to have not yet achieved the Performance and Work Behavior Targets. The purpose of this study was to see the effect of Motivation and Social Support on Employee Performance through Learning Interest. The research methodology used is quantitative descriptive with a Path Analysis approach to answer the research hypothesis. The population of this study was all PAI Non PNS as many as 125 people. The results of the study showed that both Motivation and Social Support influenced Employee Performance through Learning Interest, but Social Support did not affect Employee Performance. The research suggestion is that the Indonesian Ministry of Religion of Langkat Regency needs to strengthen the Learning Interest of PAI Non PNS because this has been proven to encourage PAI Non PNS to improve their Performance.